2019
DOI: 10.1002/fes3.189
|View full text |Cite
|
Sign up to set email alerts
|

Soil and management‐related factors contributing to maize yield gaps in western Kenya

Abstract: The solution to reducing existing yield gaps on smallholder farms lies in understanding factors limiting yield in areas with agricultural intensification potential. This study applied an integrated analysis approach comprising Classification and Regression Tree (CART), generalized linear mixed model (GLMM), and factor analysis (FA), to explain soil and management‐related factors influencing maize yield gaps, in order to enhance yields. The study was conducted in Mukuyu and Shikomoli in western Kenya, sites wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
2
6
1
Order By: Relevance
“…Overall yield-limiting factors of pears. From the perspective of soil, agronomy practice, and internal factors, our results showed that soil factors have the most significant effect on the yield of pear orchards, which is in agreement with the results of Sussy et al (2020). It is likely that soil is a direct source of nutrients for trees and directly affects the growth and development of crops (Song, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Overall yield-limiting factors of pears. From the perspective of soil, agronomy practice, and internal factors, our results showed that soil factors have the most significant effect on the yield of pear orchards, which is in agreement with the results of Sussy et al (2020). It is likely that soil is a direct source of nutrients for trees and directly affects the growth and development of crops (Song, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Because of low levels of SOC, a high productivity of maize for the study sites could not be expected without the application of synthetic fertilisers (NP). According to Munialo et al (2020), the critical values of soil TN are above 0.2% indicating soils of the study sites are poor in nitrogen and this nutrient limits the productivity of crops including maize. The average values of available P for all the study sites were below the critical levels for optimum crop yield, which ranges from 10.9 ppm to 21 ppm as revised by Bai et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Soil and management-related factors contributing to maize yield gaps in western Kenya [84] South Africa Potato 2020…”
Section: Ghana Cocoa 2020mentioning
confidence: 99%